Introduction to audiovisual archives - Stockinger, Peter (London, UK : ISTE Ltd ; Hoboken, NJ : John Wiley & Sons, Inc., 2012)
Today, audiovisual archives and libraries have become very popular especially in the field of collecting, preserving and transmitting cultural heritage. However, the data from these archives or libraries - videos, images, sound tracks, etc. - constitute as such only potential cognitive resources for a given public (or "target community"). They have to undergo more or less significant qualitative transformations in order to become user- or community-relevant intellectual goods. These qualitative transformations are performed through a series of concrete operations such as: audiovisual text s.
Context and issues / Peter Stockinger, Elisabeth de Pablo, Francis Lemaitre -- Part 1. The segmentation and description workshops for audiovisual corpora -- The segmentation workshop for audiovisual resources / Elisabeth de Pablo -- Description workshop for audiovisual corpora / Muriel Chemouny -- Analysis of the audiovisual expression / Elisabeth de Pablo and Jirasri Deslis -- Analysis of the audiovisual content / Peter Stockinger -- Uses of an audiovisual resource / Muriel Chemouny, Primuda Sakunthabai -- Model of an audiovisual publication in the form of a Web portal / Jirasri Deslis -- Part 2. Technological environment, development, and new perspectives -- The ASW digital environment / Francis Lemaitre -- The ASW Studio / Francis Lemaitre -- The technical development of the "Web portal" publishing model / Richard Guerinet.
Includes bibliographical references (pages 281-284) and index.
Print version record.
Keywords: Audio-visual archives; Audio-visual materials -- Classification; Research -- Methodology; Audio-visual archives; Audio-visual materials -- Classification; Research -- Methodology; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- Cataloging & Classification; Audio-visual archives; Audio-visual materials; Research -- Methodology; Audio-visual archives; Audio-visual materials / Classification; Research / Methodology; Electronic books; Classification